DESCRIPCION MORFOLOGICA DE LOS ESTADOS INMADUROS DE RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) - Frías L., D.; Martínez, H.; Alviña, A. (Acta Entomológica Chilena, 2022)
The morphology of the immature stages of R. tomatis was studied with optical and scanniing microscopes. The results show that the eggs, three larvae instars and pupae can be morphologically distinguished from their congeneric species, R. nova andR.conversa.